2011
DOI: 10.1029/2010jb007911
|View full text |Cite
|
Sign up to set email alerts
|

Injection of Tibetan crust beneath the south Qaidam Basin: Evidence from INDEPTH IV wide-angle seismic data

Abstract: The International Deep Profiling of Tibet and the Himalaya Phase IV (INDEPTH IV) active source seismic profile in northeast Tibet extends 270 km roughly north‐south across the Songpan‐Ganzi terrane, the predominantly strike‐slip North Kunlun Fault (along the Kunlun suture), the East Kunlun Mountains, and the south Qaidam Basin. Refraction, reflection, and gravity modeling provide constraints on the velocity and density structure down to the Moho. The central Qaidam Basin resembles average continental crust, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
144
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(159 citation statements)
references
References 72 publications
11
144
0
Order By: Relevance
“…Many studies have been performed in the Tibetan plateau, but most of the geophysical studies of the Tibetan crust and mantle structure to date have focused on the southern Kind et al, 1996;Nelson et al, 1996;Huang et al, 2000;Wei et al, 2001;Wang et al, 2003;Unsworth et al, 2005;Yao et al, 2008;Guo et al, 2009), central (Owens and Zandt, 1997;Kind et al, 2002;Tilmann et al, 2003), and eastern Tibetan plateau , with the primary objectives of understanding the continental collision process and the intrusion of the crustal and mantle materials from the Indian plate into the Eurasian plate. In comparison to other parts of the plateau, fewer seismic investigations have been done in the northeastern Tibetan plateau (e.g., Wittlinger et al, 1996;Zhu and Helmberger, 1998;Vergne et al, 2002Vergne et al, , 2003Karplus et al, 2011Karplus et al, , 2013Yue et al, 2012), which either are localized along linear profiles or focused on the velocity discontinuity structure. In our previous study (Li et al, 2012), we determined that the lowvelocity zone (LVZ) terminated around the east Kunlun fault (KLF) in the northeastern Tibetan plateau.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been performed in the Tibetan plateau, but most of the geophysical studies of the Tibetan crust and mantle structure to date have focused on the southern Kind et al, 1996;Nelson et al, 1996;Huang et al, 2000;Wei et al, 2001;Wang et al, 2003;Unsworth et al, 2005;Yao et al, 2008;Guo et al, 2009), central (Owens and Zandt, 1997;Kind et al, 2002;Tilmann et al, 2003), and eastern Tibetan plateau , with the primary objectives of understanding the continental collision process and the intrusion of the crustal and mantle materials from the Indian plate into the Eurasian plate. In comparison to other parts of the plateau, fewer seismic investigations have been done in the northeastern Tibetan plateau (e.g., Wittlinger et al, 1996;Zhu and Helmberger, 1998;Vergne et al, 2002Vergne et al, , 2003Karplus et al, 2011Karplus et al, , 2013Yue et al, 2012), which either are localized along linear profiles or focused on the velocity discontinuity structure. In our previous study (Li et al, 2012), we determined that the lowvelocity zone (LVZ) terminated around the east Kunlun fault (KLF) in the northeastern Tibetan plateau.…”
Section: Introductionmentioning
confidence: 99%
“…Although evidence for the subduction of the Indian plate appears to be sufficient, the distance of extension of the Indian crust (and/or mantle) is still unclear. As the most effective and practical geophysical methods, seismic imaging (Gao et al 2013;Karplus et al 2011;Kind et al 2002;Nabelek et al 2009;Nabelek and Nabelek 2014;Xu et al 2015a, b;Zhang et al 2011Zhang et al , 2013Zhao et al 2011Zhao et al , 2014aZhao and Nelson 1993) and magnetotelluric (MT) data modeling (Chen et al 1996;Le Pape et al 2012;Unsworth et al 2004Unsworth et al , 2005Wei et al 2001) have been widely applied to study the deep evolution and tectonic processes of the plateau over the past decades. Results of previous seismological studies have revealed some details for the extension Liang et al 2016;Tian et al 2015;Xu et al 2015a;Zhang et al 2015Zhang et al , 2016Zhang et al , 2011Zhao et al 2014b) and we believe that MT data can provide some indirect information to obtain a more comprehensive model.…”
Section: Introductionmentioning
confidence: 99%
“…The complicated distribution of fractures and faults within the folded crust of the SGT may play an important role in the generation of the observed anisotropic velocity and attenuation structures. Both the NKF and SKF likely extend into the heterogeneous upper crust probably with very low velocity and Q between them Karplus et al, 2011]. If the crustal anisotropy is the major source of the azimuthal anisotropy of 1/Q Lg estimated in our model, the upper crust of the northwestern corner of the SGT may be assumed nearly transversely isotropic with abundant parallel faults and fractures following the orientations of the NKF, SKF, and JS.…”
Section: Lg and Pg Q Tomographymentioning
confidence: 99%
“…Surface topography and Moho geometry, sediment thickness [e.g., Kennett, 1986], and inhomogeneous velocity structures of the crust can generate a complicated seismic wave field at high frequencies (> 0.5 Hz). Across the Kunlun Shan, steep topography (> 2 km), a thick sedimentary basin (> 5 km in the Qaidam), and rapid Moho depth changes (15-20 km) [e.g., Zhu and Helmberger, 1998;Karplus et al, 2011] all could lead to substantial scattering of the Lg wave field. Previous studies have observed an energy loss of Lg when its path laterally crosses the Kunlun Shan [Zhao et al, 2003], which is probably associated with large geometrical fluctuations along this mountain range.…”
Section: Lg and Pg Q Tomographymentioning
confidence: 99%